2018
DOI: 10.1136/thoraxjnl-2017-211073
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic phenotype of skeletal muscle in early critical illness

Abstract: NCT01106300.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(178 citation statements)
references
References 56 publications
7
167
0
4
Order By: Relevance
“…[47][48][49][50] Mitochondrial myopathy has been suggested to play an important role in the skeletal muscle dysfunction, and poor physical functioning common in patients with CKD. ***Denotes P < .001 vs healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] Mitochondrial myopathy has been suggested to play an important role in the skeletal muscle dysfunction, and poor physical functioning common in patients with CKD. ***Denotes P < .001 vs healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the acute illness determines the degree of muscle wasting,51 with age, ICU length of stay, systemic inflammation and chronic health prior to critical illness determining the trajectory of recovery 58. In addition, decreased mitochondrial biogenesis and dysregulated lipid oxidation contribute to a compromised skeletal muscle bioenergetic status with intramuscular inflammation associated with impaired anabolic recovery60 and development of ICU-acquired weakness 61. Future clinical work will need to focus on these key areas with the establishment of the appropriate timing, dose and frequency of both pharmacological and non-pharmacological treatments.…”
Section: Early Rehabilitation During Critical Illnessmentioning
confidence: 99%
“…In the inflammatory setting, pyruvate dehydrogenase, which serves as the key gatekeeper to the Krebs cycle, is inhibited, and carbohydrate metabolism is shunted toward anaerobic pathways, resulting in lactate production . Lipogenesis is inhibited, and mitochondrial β‐oxidation of fat may be impaired, resulting in the inability to utilize fat during this period . As a result, proteolysis (predominately from lean body mass) becomes a primary contributor for ongoing substrate provision.…”
Section: The Hypermetabolic Response In Burn Patientsmentioning
confidence: 99%
“…The time frame by which the assault on skeletal muscle occurs is swift. A 2018 study by Puthucheary et al demonstrated decreased intramuscular ATP 1 day following an inflammatory insult, potentially related to the intentional redirection of substrate to fulfill alternative fuel requirements . Skeletal muscle becomes a source of amino acids both as precursors for gluconeogenesis and later as substrate for the healing of burn wounds .…”
Section: The Hypermetabolic Response In Burn Patientsmentioning
confidence: 99%
See 1 more Smart Citation